A Doutrina da Criação na teologia de Calvino e Barth: A semelhança do método como fundamento da releitura teológica barthiana. - Souza Filho, Adilson de (2004)
John Calvin is the first name that comes to our mind as we mention the 16th Century Protestant Reformation. His influence in Geneva and especially his even most famous and important theological work called Institutes of the Christian Religion, which served and still serve as a doctrine manual to Calvinists, attest Calvin s relevance to the Protestantism. In the Institutes, Calvin reinterpreted all the Christian church theological dogmas. The dogma of Creation is given a special place in his work, as they serve as a starting point for Calvin to study two other equally important dogmas, which are Revelation and Salvation in Christ. The main characteristic found in Calvin s dogma of Creation is God s sovereign majesty. By the way, this way of viewing God s sovereignty marked the Protestantism movement very strongly and is still present in the reformed tradition. If John Calvin is the first name in Protestant Reformation, Karl Barth is most likely the first name in all reformed tradition. Like Calvin, Barth also reinterpreted all the dogmas of the Christian church. Of his many works, Die Kirchliche Dogmatik is certainly his most remarkable one. Consisting of more than 9,000 pages, it served and still serves significantly as a dogmatic reference source to Protestantism. The main characteristic of Karl Barth s Creation dogma is found in God s pact of grace. My research focused the dogma of Creation as reinterpreted by Calvin and Barth. According to my view, Barth approached Calvin in his theology, first of all because he is Calvinist himself, and secondly because his later theological phase is exclusively marked by dogmatism. In this work, I tried to develop the common points that I have found between Barth and Calvin, as for example, in the similarity of the theological method, which will also be the basis for my proposal of Barth s dogma of Creation as a new reading of Calvin s own dogma of Creation.(AU)